Habitat Preference of Asiatic Elephant (Elephas maximus) in Periyar Tiger Reserve, South India - Srivastava, K. K.; Zacharias, V. J.; Bhardwaj, A. K.; Hameed, S. V. Abdul (Indian Forester, 1995)
A study of the Asiatic Elephants (Elephas maximus) was conducted in and around the Periyar Tiger Reserve on the habitat preference of the species during various seasons for the management of Elephant.